Bronchial mucormycosis, an unusual finding on bronchoscopy: Bronchial mucormycosis (Actualizaciones en Sida e Infectología, 2023)
Mucormycosis is an infection caused by opportunistic fungi belonging to the order Mucorales. Since the SARS CoV 2 pandemic, warnings have been issued about the increase in the presentation of this infection. The presentation of tracheobronchial mucormycosis represents 37% of pulmonary involvement.We present the clinical case of a diabetic patient with severe pneumonia due to SARS VOC 2, with unfavorable evolution, who was taken to bronchoscopy and found whitish pseudomembranes obstructing the lumen of the left main bronchus, confirming histopathologically the presence of mucormycosis.A report of the present case is made to recognize the appearance of fungal infections in patients with poorly controlled diabetes and SARS COV 2 infection, who have a torpid evolution. The presence of white pseudomembranes should be an alarm sign to have this type of infections within the diagnostic possibilities.
Keywords: Diabetes mellitus; mucormycosis; SARS CoV 2